2020
DOI: 10.1038/s41598-020-72949-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal gestational weight gain and preterm birth according to body mass index and maternal age in Quzhou, China

Abstract: The aim of this study is to investigate the association between maternal gestational weight gain (GWG) and preterm birth according to pre-pregnancy body mass index (BMI) and maternal age. We did a cohort, hospital-based study in Quzhou, South China, from 1 Jan 2018 to 30 June 2019. We selected 4274 singleton live births in our analysis, 315 (7.4%) of which were preterm births. In the overall population, excess GWG was significantly associated with a decreased risk of preterm birth compared with adequate GWG (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…As in most previous studies, we found that insufficient GWG significantly increased the risk of PTB, especially among pregnant women classified as underweight or normal weight. We did not find an association between excessive rate of GWG and PTB risk; however, the risk increased if women had a low PP-BMI, which is consistent with some studies [11,25]. Although the biological mechanism is not clear, it can be considered that a reasonable GWG during pregnancy can effectively reduce the risk of PTB, especially for pregnant women with low PP-BMI.…”
Section: Comparison With Previous Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…As in most previous studies, we found that insufficient GWG significantly increased the risk of PTB, especially among pregnant women classified as underweight or normal weight. We did not find an association between excessive rate of GWG and PTB risk; however, the risk increased if women had a low PP-BMI, which is consistent with some studies [11,25]. Although the biological mechanism is not clear, it can be considered that a reasonable GWG during pregnancy can effectively reduce the risk of PTB, especially for pregnant women with low PP-BMI.…”
Section: Comparison With Previous Studiessupporting
confidence: 87%
“…First, given the potential confounding bias, our study used a cohort of motherchild pairs with a one-and-a-half-year follow-up, and only women lacking undisputed high-risk factors for PTB were included in the study. Several studies used retrospective designs to investigate the association between GWG and PTB, which maybe a source of bias [25][26][27]. While most previous studies used statistical methods to correct for research bias caused by other high-risk factors of PTB, we excluded the PTB high-risk group from the beginning of the cohort study to accurately describe the relationship between GWG and PTB.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…Participants reported their pre-pregnancy weight (kg) at the time of enrollment and trained obstetricians measured weight during pregnancy a median of 10 times (range, [5][6][7][8][9][10][11][12][13][14][15][16][17]. The obstetricians measured each participant's weight twice and calculated the average value of the two measurements.…”
Section: Outcomes: Gestational Weight Gainmentioning
confidence: 99%
“…The epidemic of excessive gestational weight gain (EGWG) during recent decades has led to a high incidence of adverse maternal and child health outcomes, such as gestational diabetes mellitus, cesarean delivery, and childhood obesity [1][2][3][4]. The prevalence of EGWG in China varies from 27.5−44.5% based on the geographic region [5,6] and has become a serious public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in gestational age, GWG is a normal physiological process of pregnancy development [13]. Adequate GWG can reduce the incidence of maternal and neonatal complications [14][15][16]. In 2009, the Institute of Medicine (IOM) published GMG guidelines and developed different criteria for GWG of singleton and twin pregnant women to promote GWG control in the normal range [17].…”
mentioning
confidence: 99%